2018
DOI: 10.1139/cjps-2017-0301
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrogen fixation by irrigated dry bean (Phaseolus vulgaris L.) genotypes

Abstract: Dry bean (Phaseolus vulgaris L.) is usually considered to be poor at biological nitrogen fixation (BNF), but large variations in this trait have been observed among bean genotypes. We evaluated 16 bean genotypes for N2 fixation ability in four N treatments: (i) uninoculated in low-N soil (30 kg N ha−1), (ii) inoculated with commercial Rhizobium leguminosarum bv. phaseoli inoculant Nitrastik-D® in low-N soil, (iii) inoculated with commercial R. leguminosarum bv. phaseoli inoculant Nodulator® in low-N soil, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A number of studies have shown that nodulation is inhibited in soybean by nitrogen levels exceeding 5 mM (Saito et al, 2014). In a recent study, evaluating 16 common bean genotypes from different market classes under four nitrogen treatments [not inoculated low N (30 kg ha −1 ) and high N (100 kg ha −1 ) and two rhizobia strains], Akter et al (2018) confirmed inhibition of nitrogen fixation by a high dose of nitrogen fertilizer. Genotype-specific sensitivity of nitrogen fixation to mineral nitrogen was identified in common bean (Hardarson, 1993;Farid et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…A number of studies have shown that nodulation is inhibited in soybean by nitrogen levels exceeding 5 mM (Saito et al, 2014). In a recent study, evaluating 16 common bean genotypes from different market classes under four nitrogen treatments [not inoculated low N (30 kg ha −1 ) and high N (100 kg ha −1 ) and two rhizobia strains], Akter et al (2018) confirmed inhibition of nitrogen fixation by a high dose of nitrogen fertilizer. Genotype-specific sensitivity of nitrogen fixation to mineral nitrogen was identified in common bean (Hardarson, 1993;Farid et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Biological N fixation by legumes (e.g., faba bean, lentil, pea, chickpea, alfalfa, red clover etc.) ranges from 21 to 389 kg ha −1 (Table 1) (Cazzato et al 2012;Nimmo et al 2013;Büchi et al 2015;Hossain et al 2016;Snapp et al 2017;Akter et al 2018;da Silva Júnior et al 2018;Dhamala et al 2018;Ntatsi et al 2018;Pampana et al 2018;Ntatsi et al 2019).…”
Section: Nitrogen Supply Via Biological Nitrogen Fixation (Bnf)mentioning
confidence: 99%
“…The N 2 -fixation capacity of legumes (e.g., the proportion of N derived from the atmosphere [%Ndfa] and biomass productivity) is mainly dependent on plant species, genotypes, symbiotic bacteria (e.g., Rhizobium spp.) strains, and environmental conditions (Büchi et al 2015;Hossain et al 2016;Akter et al 2018;Ntatsi et al 2018;Benjelloun et al 2019;Ntatsi et al 2019).…”
Section: Nitrogen Supply Via Biological Nitrogen Fixation (Bnf)mentioning
confidence: 99%
“…The combination of enhanced SNF with the capacity to better acquire or utilize soil N should improve adaptation of beans to unfertile soils. Bean genotypes that combine greater SNF and nitrogen use efficiency would reduce both dependence on N fertilizer and potential contamination of N in the environment (Akter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%